Optimization of Central Air Conditioning Plant by Scheduling the Chiller Ignition for Chiller Electrical Energy Management - Nugraha, Anggara Trisna; Safitri, Lailia Nur; Zakariz, Naufal Praska (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Currently, the demand for electrical energy in homes, buildings, and industry is increasing, in line with population and economic growth. Of course, because of the massive use of electrical energy, it is necessary to increase efficiency. Large shopping malls in some countries are the biggest consume electricity, especially when it comes to cooling systems. Therefore, it is necessary to save energy in shopping centers. Because there are still few tenants and shopping centers that are relatively quiet, the mall's energy consumption is low, so it requires increasing energy-efficient consumption efficiency by optimizing power management and calculating the chiller performance coefficient (COP). This research aims to increase the chiller performance coefficient (COP) to save energy in shopping centers. The optimization method used is to make changes to the chiller ignition schedule when it's used in malls. Through the analysis from this research, it was found that the COP increased to 0.584, and the value before optimization was 6.181. With increasing COP, the chiller performance will increase. The effect of increasing the chiller's performance could optimize the electrical energy efficiency of the chiller in 138.82 kWh / day